A psycholinguistic method for measuring coarticulation in child and adult speech - Howson, Phil J. (Behav Res Methods, 2021)
A perceiver’s ability to accurately predict target sounds in a forward-gated AV speech task indexes the strength and scope of anticipatory coarticulation in adult speech [Redford et al., 2018, JASA]. This suggests a perceptually-based method for studying coarticulation in populations who may poorly tolerate the more invasive or restrictive techniques used to directly measure speech movements. But the use of perception to measure production begs the question of confounding influences on perceiver performance and thus on the reliability and generalizability of the proposed method. The present study was therefore designed to test whether a gated AV speech method for measuring coarticulation provides reliable results across different study populations (child versus adult), different task environments (in lab versus online), and different coarticulatory directions (forward/anticipatory versus backward/carryover). The results indicated excellent measurement reliability across age groups in the forward/anticipatory measurement direction, though more perceivers are needed to achieve the same levels of agreement and consistency when the task is completed online. Accuracy was lower in the backward/carryover direction; and, although agreement and consistency across perceivers was still reasonably high, the effect of age group was different in the laboratory and online environments, suggesting measurement error in one or both environments. Overall, the results support using in-lab or online perceptual judgments to measure anticipatory coarticulation in developmental studies of speech production. Further validation study is needed before the method can be extended to measure carryover coarticulation.